The Analysis of Interpersonal Conflict Between Finch And Violet As The Main Character In Film All The Bright Places (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study examines the representation of interpersonal and institutional conflicts in the film All the Bright Places (2020). While existing literature often focuses on the romanticization of adolescent trauma, this research explores the socio-cultural dimensions of mental health. The primary objective is to identify emotional tensions between characters and reveal how social and family institutions contribute to psychological struggles. Using a qualitative narrative approach, scenes, dialogues, and visual elements were interpreted as cultural texts. The findings indicate that the interpersonal conflict between Finch and Violet arises from mismatched emotional needs—Finch seeking stability through closeness and Violet requiring space for grief. However, this tension escalates into a fatal psychological crisis due to institutional conflict, characterized by the failure of the school and family to provide adequate support. The school frames mental health as a disciplinary issue, while the family remains emotionally unresponsive, reinforcing the characters' alienation. The study concludes that adolescent trauma is a dialectical outcome of individual experience and institutional neglect rather than a purely personal psychological matter. It critiques the cultural normalization of adolescent emotional resilience and emphasizes that mental health is a collective social responsibility. These results suggest that love alone cannot substitute for the necessary systemic institutional support in addressing adolescent mental crises.